The Criminalisation and Imprisonment of Migrant Victims of Trafficking - Hales, Liz (Oñati Socio-Legal Series, 2018)
This paper outlines the key elements of research that was carried out between 2010 and 2011 at the Institute of Criminology, University of Cambridge by Hales and Gelsthorpe (2012) on the Criminalisation of Migrant Women in terms of goals, research methods, key findings and resultant policy and practice implications. It then goes on to document developments in the UK since publication of the findings and conclusions that we can draw from these in terms of meeting the challenges of combatting human trafficking.